Genetic insights into the effect of trace elements on cardiovascular diseases: multi-omics Mendelian randomization combined with linkage disequilibrium score regression analysis - Chen, Bohang; Wang, Chuqiao; Li, Wenjie (Frontiers in Immunology, 2024)
ObjectiveEpidemiological evidence indicates that trace elements are significantly associated with cardiovascular health. However, its causality and underlying mechanisms remain unclear. Therefore, this study aimed to investigate the causal relationship between trace elements and cardiovascular disease, as well as their potential mechanism of action.MethodTwo-sample Mendelian randomization (MR) analyses along with mediated and multivariate MR analyses were employed. These analyses utilized 13 trace elements as exposure variables and 20 cardiovascular diseases as outcome variables, with 4907 circulating plasma proteins, 1400 serum metabolites, 731 immune cell phenotypes, and 473 intestinal flora as potential mediators. The Bayesian weighted MR method was used to validate the MR results, and linkage disequilibrium score regression (LDSC) was applied to explore the genetic correlation between trace elements and cardiovascular disease.ResultOur findings indicated a positive or negative causal relationship between genetically predicted trace elements and cardiovascular disease. An analysis using the Bayesian weighted MR method demonstrated that our causal inference results were reliable. The results of the mediated MR analyses indicate that potassium may reduce the risk of ischemic heart disease by influencing the expression of the plasma proteins BDH2 and C1R. Vitamin B12 may increase the risk of coronary atherosclerosis and cardiovascular death by reducing the levels of VPS29 and PSME1 proteins, while vitamin C may mitigate the risk of cardiac arrest by inhibiting the expression of the TPST2 protein. In addition, potassium can reduce the risk of ischemic heart disease by lowering 4-methoxyphenyl sulfate levels. None of the instrumental variables exhibited pleiotropy in the MR analysis. A sensitivity analysis using the leave-one-out method further confirmed the robustness of our findings. LDSC results indicated a genetic correlation between multiple trace elements and various cardiovascular diseases.ConclusionThis study uncovered the true causal relationship between trace elements and cardiovascular disease risk using genetic methods, and revealed the significant mediating role of specific plasma proteins and metabolites in this relationship.